Comparative unfolding of the Trp-cage miniprotein in anionic and cationic surfactants - Osita Sunday Nnyigide; Haewon Byeon; Uchenna Esther Okpete (PLoS ONE, 2026)
This study investigates the effects of anionic sodium dodecyl sulphate (SDS) and cationic cetyltrimethylammonium bromide (CTAB) surfactants on the stability of the Trp-cage miniprotein in aqueous solution at varying concentrations and temperatures. Conformational dynamics were analyzed using principal component–based free-energy landscapes, cluster population analysis, and radial distribution functions. The results show that at 25 °C in water, the protein adopts a compact native basin, whereas at 100 °C it exhibits expanded conformational space with multiple metastable states. The presence of surfactants further modulates this behavior in a concentration-dependent manner. Cluster population analysis shows that SDS promotes a highly heterogeneous ensemble characterized by reduced dominance of the native-like cluster, while CTAB partially protects the protein from thermal denaturation at higher concentrations. Radial distribution functions demonstrate strong accumulation of SDS headgroups around the protein and pronounced insertion of SDS alkyl tails into hydrophobic protein regions, indicating direct hydrophobic destabilization and micelle-assisted unfolding. In contrast, CTAB exhibits weaker headgroup association owing to electrostatic repulsion and reduced tail–hydrophobic contacts, suggesting a less disruptive interaction mechanism. At high concentration, CTAB aggregates provide a structured hydrophobic environment that stabilizes the folded state and suppresses denaturation. Together, these results provide a molecular-level picture of how surfactant chemistry and concentration govern the conformational stability of a cationic protein, highlighting the dominant role of hydrophobic interactions in surfactant-induced denaturation at high temperature.